The Effect Of Perceived Organization Support and Work Motivation On Employee Engagement In Improving Employee Performance At Regional Revenue Agency In Tegal Regency - Setya Yurissa Putra; Edy Raharja (Politeknik Siber Cerdika Internasional, 2023)
The purpose of this research is to test the influence of perceived organizational support, and work motivation on employee engagement to impact employee performance. Using these variables, the use of these variables is able to solve the problems arising withinemployees of the Regional Revenue Agency of Tegal Regency. The statement of this problem is how to increase employee performance?. The sample size of this research is 44employees of the Regional Revenue Agency of Tegal Regency. Using the Smart PLS (Path Least Square). The results show that perceived organizational support and work motivation on employee engagement impact employee performance. The effect ofperceived organizational supporton employee engagement are significant;the effect ofwork motivationon employee engagement are significant;the effect ofperceived organizational supporton employee performance are significant;the effect ofwork motivation on employee performance is significant;the effect ofemployee engagementon employee performance is significant.